The sectoral effect of demonetization on the economy: Evidence from early reaction of the Indian stock markets - Mohammad Shameem Jawed; Amol Dhaigude; Archit Vinod Tapar (Cogent Economics & Finance, 2019)
We investigate the impact of the Demonetization of 85% currency in circulation in India on the eve of 8 November 2016 on all the listed stocks spanning over 20 broad industry clusters (sectors) and their affiliation type from the Indian economy over the period of November to Mid-January 2016. Using the event study methodology, we assess the effects of Demonetization, relative to what had been anticipated, as measured by abnormal returns (ARs). The results indicate that Group Affiliated firms witnessed the highest negative abnormal returns both on the event days and during the event window period, while PSUs witnessed the least wrath. On the sectoral front, Demonetization shows a mixed effect in the early days which changes to positive for most of the sectors barring a few. Banking Sector was the worst hit in the early days with a CAAR of −1.74%, while many sectors like Pharma, Paper and Wholesale Trading witnessed a windfall gain in the long run.
Keywords: 330; event study; demonetization; sectorial analysis; black money; India